ANALISIS PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, MANFAAT, DAN RISIKO TERHADAP MINAT BERKELANJUTAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna GoPay di Semarang) - Nur Amalia Syabila; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the Effect of Perceived usefulness, Perceived Eaese of Use, and Perceived Risk on Continuance Intention with Trust as an intervening variable for GoPay users in Semarang. The population in this study were users of the GoPay digital wallet (e-wallet) who had use GoPay in Semarang. The number of samples used in this study were 125 respondent who are currently or domiciled in Semarang with a minimun aged 17 years, and who had made GoPay transactions 2 times in the last 1 month. The sampling method used in this research is purposive sampling technique. The data collection method is done by distributing online questionnairies via google form. The research uses Structural Equation Modeling (SEM) analysis technique with AMOS program as an analytical tool. The results of this study indicate that perceived usefulness, perceived ease of use, and perceived risk have a positive and significant effect on trust. Furthermore, perceived usefulness and perceived risk have a positive influence but cannot influence to continuance intention. Meanwhile, perceived ease of use has a negative and not significant effect on continuance intention. Then finally, trust can mediate the relationship between variables perceived usefulness, perceived ease of use, and perceived risk on e-wallet continuance intention.